2017
DOI: 10.18632/oncotarget.21695
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents peritendinous fibrosis by inhibiting transforming growth factor-β signaling

Abstract: Injury-induced peritendinous adhesion is a critical clinical problem that leads to tendon function impairment. Therefore, it is very urgent to explore potential approaches to attenuate peritendinous adhesion formation. Recently, several studies have demonstrated the biological effect of metformin in inhibiting multiple tissue fibrosis. In this study, we performed in vitro and in vivo experiments to examine whether metformin prevents injury-induced peritendinous fibrosis. We found that tendon injury induced sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
(56 reference statements)
1
27
0
Order By: Relevance
“…To further investigate the mechanisms underlying miR-21-5p-induced fibrogenesis in tenocytes, we chose Smad7 as a candidate gene because of its close involvement in inflammation and fibrosis 35, 36, 50, 51. Previous studies have demonstrated that TGF-β1/SMAD signaling contributes to the formation of adhesions around healing digital flexor tendons9, 52 and that blocking of the TGF-β1 pathway could prevent the formation of tendon adhesions 38 . Our transfection data revealed that BMDM exosomes containing mostly miR-21-5p reduced Smad7 expression, suggesting that exosomal miR-21-5p could activate the TGF-β1 pathway in tendon by reducing Smad7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the mechanisms underlying miR-21-5p-induced fibrogenesis in tenocytes, we chose Smad7 as a candidate gene because of its close involvement in inflammation and fibrosis 35, 36, 50, 51. Previous studies have demonstrated that TGF-β1/SMAD signaling contributes to the formation of adhesions around healing digital flexor tendons9, 52 and that blocking of the TGF-β1 pathway could prevent the formation of tendon adhesions 38 . Our transfection data revealed that BMDM exosomes containing mostly miR-21-5p reduced Smad7 expression, suggesting that exosomal miR-21-5p could activate the TGF-β1 pathway in tendon by reducing Smad7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Peritendinous fibrosis, a unique pathological tissue fibrosis, mostly occurs after tendon injury, tendon surgery, and joint immobilization. Several mechanisms have been implicated in the modulation of adhesion formation, including the regulation of the inflammatory response ( Chen et al, 2017 ), and the TGF signaling pathway ( Jiang et al, 2014 ; Zheng et al, 2017 ). The present study, for the first time, to our knowledge, examines the relationship between autophagy and peritendinous fibrosis, and demonstrates protective roles of autophagy in fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another lncRNA, HOXD-AS1, has been reported to upregulate JAK/STAT target genes, including COX-1 and caspase-1 [21]. In recent years, aberrant arrest of the cell cycle has been shown to be critical in fibrogenesis; additionally, excessive cell proliferation and increased G2/M arrest have been observed in peritendinous fibrosis [22]. Furthermore, Li showed that Atg5 interference promoted G2/M phase arrest in proximal tubular epithelial cells and exacerbated subsequent renal fibrosis [23].…”
Section: Discussionmentioning
confidence: 99%